Identification of Escherichia coli in Ice Dawet Sold in the Palu City Area - Yosphita Sevianti; I Nengah Kundera; Musdalifah Nurdin; Yulia Windarsih; Abdul Ashari; Mohammad Jamhari (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Escherichia coli is a Gram-negative bacterium from the family Enterobacteriaceae found in the human body and is used as an indicator of hygiene in water, food, or beverages. The purpose of this study was to identify the presence of E. coli in ice dawet sold in the Palu City area. This study used a descriptive-exploratory design with the Most Probable Number (MPN) method, Total Plate Count (TPC), and biochemical testing using Triple Sugar Iron Agar (TSIA) medium. Samples were collected from five locations in the Palu City area using simple random sampling. Based on the results, the Most Probable Number (MPN) test produced an average value of 18.700 MPN/mL of sample, while the Total Plate Count (TPC) test showed an average value of 26.800 CFU/mL of sample, indicating that the samples did not meet the standards set by the Indonesian National Standard (SNI) under the Ministry of Health, which states that the maximum allowable microbial contamination in beverages is 0/100 mL. Confirmatory tests on Eosin Methylene Blue Agar showed colony growth with a metallic green sheen and reddish coloration, characteristic of Gram-negative bacilli. The results of the Triple Sugar Iron Agar biochemical test were positive, indicating biochemical characteristics consistent with E. coli. Therefore, the findings confirm the presence of E. coli in the analyzed samples.